Linear Approximation-Based Weighted Frequency Hopping Scheme for Sharing Radar Band - Choi, Sunjoo; Baek, Hoki; Lim, Jaesung (International Conference on ICT Convergence, 2020)
Spectrum sharing has been studied to solve the problem of spectrum scarcity. The spectrum sharing technique should consider the characteristics of both the primary user (PU) and the secondary user (SU). Studies considering a radar as PU have only focused on spectrum sharing with SU by using a fixed frequency system. To the best of our knowledge, there is a lack of research that considers the pulse collision probability on spectrum sharing between radar and frequency hopping communication systems (FHCS). In this paper, we propose a linear approximation-based weighted frequency hopping (LAWFH) scheme to reduce pulse collision probability. In the LAWFH scheme, all channels belonging to the radar band are categorized to used and unused channels. We estimate a frequency-hopping weight (FHW) by using a linear approximation to construct frequency-hopping patterns, in which the unused channels appear more than the used channels. We construct a mathematical model for analyzing the pulse collision probability of the LAWFH scheme to prove the performance of LAWFH.
Keywords: Fixed frequency; Frequency hopping communication; Frequency hopping pattern; Linear approximations; Primary users; Pulse collision; Secondary user; Spectrum sharing; frequency hopping; radar; spectrum sharing